Analisis Pengaruh Media Sosial (Facebook) Terhadap Pola Kebahasaan Pada Mahasiswa Fakultas Sastra dan Budaya Universitas Khairun - Ikmal Muhammad (TEKSTUAL, 2021)
Progress of information technology and communications bear creation peripheral of sophisticated communications and can penetrate room boundary and time. one of them  is  internet.Attendance of internet can form world society become incircuit globally or which more knowledgeable as community cyber. where passing the the room happened various penetration and transfer of culture complexly. One of them language. Social media of facebook is one of the application friendship of which can become example  what a passive is friction of culture and way of communications, the core important is youngster, this matter is started from usage of Ianguage as instrument which is used in communications of facebook.Most Society group affect is youngster nowadays, insoluble especially to technology, including student faction with Ianguage study background even if. For the reason activity in the form  giving of socialization with a purpose to give the understanding of to condition of contempore concerning influence of facebook to usage of Ianguage in interaction in social media of facebook become important to be conducted. Through discourse and demonstration vary, student given by the understanding of hitting influence of facebook to Ianguage aspect in student scope in faculty of letters and culture as an real example of which easierly digested.This matter is conducted on the chance of can give effect, especially at its applying in actifity in  facebook. Because however, especially faculty of letters and culture students which is have Ianguage study background to have responsibility to know to regarding contemporary Ianguage phenomenon which in this time is happened, particularly systematically such phenomenon can affect socially in its life.